Best Practices of Heritage and Gastronomic Tourism in a Kampong - Muhrofi-G, Kun Aniroh; Maria, Rina Rifqie (E-Journal of Tourism; Volume 4 Number 2 (September 2017), 2017)
Kampong as a center of local culture keeps endless-life values that can be explored as a learning resource. In kampong there are genuine values of life which is full of local wisdom that has already existed since the ancient time. People in a kampong in Malang, think simply and use symbols in foods and life values which have been conducted by their ancestors. Culinary and heritage in the form of precious life values are two practices among many which have existed for years until the present time. However, the young generation who inherits the practices from their parents mostly do not know the philosophy or the lesson learned why they are doing these things. This paper aims at analyzing culinary and heritage values in a kampong by arranging in a calendar of events, exploring the philosophy and creatively packing the practices in a kampong for the culinary tourism purposes.